Local Self-Government in the System of Modern Public Administration - Kovalenko, N. (Pressing Problems of Public Administration, 2019)
The current stage of forming a social and law state is impossible without reorganizing the system of local self-government, taking into account global changes and democratic principles. Considering the organizational and legal foundations of local councils activities, it is necessary to pay attention to the fact that they, as an element of the public administration system, are included in its important subsystem - local self-government. The purpose of the article is to determine the specifics of local self-government in the system of modern public administration and directions of its modernization taking into account the current changes in the socio-economic status of the country. Local self-government should be seen as an important element of the public administration system, bearing in mind that apart from the “classical” form of public administration, it is the management of special bodies and officials that it is widely used in various forms of direct democracy to address issues in which population is interested in. The most important issue, which allows to determine not only the place of local self-government in the public administration system, but also to reveal the special essence of this level, should be the process of institutionalization of local self-government as an institution of public administration, which has unique institutional features. Nowadays the institutionalization process can be seen as a set of three stages that (in a meaningful way) represent the evolution of elements of the local governance system into a single emergent system, united on the basis of implementation of deliberative and participatory procedures, and based on the principles of legitimacy, transparency and legitimacy. In connection with this, the article deals with the specifics of the development of local self-government in terms of different approaches to public administration. It can be implemented in three forms: direct governance through the procedures of direct democracy, participation through the procedures of deliberative and participatory democracy. The features and possibilities of their implementation in Ukraine are also identified.